2020
DOI: 10.1186/s13063-020-4181-y
|View full text |Cite
|
Sign up to set email alerts
|

Increasing access to CBT for psychosis patients: a feasibility, randomised controlled trial evaluating brief, targeted CBT for distressing voices delivered by assistant psychologists (GiVE2)

Abstract: Background: The National Institute for Health and Care Excellence (NICE) recommends that Cognitive Behaviour Therapy for psychosis (CBTp) is offered to all patients with a psychosis diagnosis. However, only a minority of psychosis patients in England and Wales are offered CBTp. This is attributable, in part, to the resource-intensive nature of CBTp. One response to this problem has been the development of CBTp in brief formats that are targeted at a single symptom and the mechanisms that maintain distress. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
0
8
2
Order By: Relevance
“…The published study protocol 11 is briefly described here. This was a feasibility RCT with a three-arm, parallel-group design and 1:1:1 allocation, comparing GiVE and treatment as usual (the study intervention) to supportive counselling and treatment as usual (the control intervention) to treatment as usual alone, recruiting across two sites, with blinded post-treatment and follow-up assessments.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The published study protocol 11 is briefly described here. This was a feasibility RCT with a three-arm, parallel-group design and 1:1:1 allocation, comparing GiVE and treatment as usual (the study intervention) to supportive counselling and treatment as usual (the control intervention) to treatment as usual alone, recruiting across two sites, with blinded post-treatment and follow-up assessments.…”
Section: Methodsmentioning
confidence: 99%
“…There were minimal changes to the design after trial commencement, and details are reported in the study protocol. 11 The trial was registered with the ISRCTN registry (number 16166070) on 5 February 2019 ( ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…frontline practitioners, assistant psychologists). We are currently exploring the efficacy of GiVE delivered by assistant psychologists as part of a feasibility trial (Hayward et al, 2020).…”
Section: Discussionmentioning
confidence: 99%